Sustitución parcial de la harina de trigo (Triticum SPP) por la harina de banano (Musa Cavendish), y su influencia en las características reológicas de la masa (elasticidad y tenacidad) para la elaboración de pan común. - Loja Macas, José G. (2015)
The objective of this research was the partial substitution of wheat flour (Triticum spp) with bananaflour (Musa cavendish) and its influence on the rheological properties of the dough (elasticity and toughness) for making bread, bananas are considered a promising crop with a wide variety of applications particularly in the food science.